HUBUNGAN ANTARA KETUBAN PECAH DINI DENGAN KEJADIAN ASFIKSIA DAN SEPSIS NEONATORUM - Ilu Salsabila Sefin (Jurnal Medika Hutama, 2022)
Premature rupture of membranes (PROM) is one of the most common pregnancy complications. PROM is the rupture of the membranes before there are signs of labor. PROM is also one of the causes of morbidity and mortality in obstetrics. The causes of neonatal morbidity associated with PROM include asphyxia and neonatal sepsis. The purpose of this study was to determine the relationship between premature rupture of membranes and the incidence of asphyxia and neonatal sepsis. The research method used is literature review from several national and international journals which are then summarized into a topic of discussion and presented in articles. The results of the study showed a significant relationship between PROM and the incidence of neonatal asphyxia and neonatal sepsis.